ANALISIS PERGESERAN MAKNA DALAM PENERJEMAHAN SUBTITLE VIDEO KARTUN ARAB “JUHA DAN HUMA: SHAID AS-SAMAK” PADA CHANNEL AL-WADIH MEDIA - Sabingatun Dewi Masitoh (Faculty of Humanities UIN Maulana Malik Ibrahim Malang, 2024)
The shift in meaning in translation is a tendency for translation that is not the same as the literal meaning but the meaning is still maintained according to BSu. The goal is that the BSu offering can be easily and clearly accepted by BSa. This trend often occurs, especially in the translation of Arabic-Indonesian translation. In this study, we will discuss the shift in meaning that occurs in one of the famous Arabic cartoon videos ”Juha dan Huma: Shaid As-Samak”, with a duration of 00:03:53 on Al-Wadih Media Channel. The goal to be achieved is to find out the number and cause of the transformation that occurs in the translated video. This study uses the qualitative description method. The technique of collecting data in this study is to research and record, and then continue the analysis until a result is obtained. The theory used is the theory of changing meaning according to Simatopang. The results of the study showed that 23 data have changed. The shift from general meaning (G) to defined meaning (sp) 7 was 30.43%. The shift from the specific meaning (Sp) to the general (G) was 5 at 21.74%; and shifts due to cultural perspectives (SPB) was 11 at 47.83%.